2020
DOI: 10.3390/molecules25194504
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Redox-Mediated Cell Death in ER-Positive and ER-Negative Breast Cancer Cells by a Copper(II)-Phenolate Complex: An In Vitro and In Silico Study

Abstract: This research was aimed at finding the cytotoxic potential of the mixed ligand copper(II) complex [Cu(tdp)(phen)](ClO4)—where H(tdp) is the tetradentate ligand 2-[(2-(2-hydroxyethylamino)-ethylimino)methyl]phenol, and phen is 1,10-phenanthroline—to two genotypically different breast cancer cells, MCF-7 (p53+ and ER+) and MDA-MB-231 (p53- and ER-). The complex has been already shown to be cytotoxic to ME180 cervical carcinoma cells. The special focus in this study was the induction of cell death by apoptosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…Herein, the cellular effects of complex 1 , a ternary copper(II) complex containing 4-fluorophenoxyacetic acid hydrazide and 1,10-phenanthroline as ligands was evaluated on prostate cells, and the mutagenic/recombinogenic and anticarcinogenic potential of this compound were recorded in D. melanogaster . In the literature, several studies with copper(II) complexes with N , N -donor ligands ( Table 2 ), such as 1,10-phenanthroline and 2,2-bipyridine, have shown promising antitumor effects [ 10 , 27 , 28 , 29 , 30 , 31 , 32 ] and, in our study, complex 1 was selective for the LNCaP lineage, downregulating Ki-67 and Cyclin D1. In PCa, Ki-67 expression has been related to the Gleason score, lower disease-free survival, tumor invasion into the seminal vesicles, and biochemical recurrence or even death after radical prostatectomy [ 33 ].…”
Section: Discussionsupporting
confidence: 60%
“…Herein, the cellular effects of complex 1 , a ternary copper(II) complex containing 4-fluorophenoxyacetic acid hydrazide and 1,10-phenanthroline as ligands was evaluated on prostate cells, and the mutagenic/recombinogenic and anticarcinogenic potential of this compound were recorded in D. melanogaster . In the literature, several studies with copper(II) complexes with N , N -donor ligands ( Table 2 ), such as 1,10-phenanthroline and 2,2-bipyridine, have shown promising antitumor effects [ 10 , 27 , 28 , 29 , 30 , 31 , 32 ] and, in our study, complex 1 was selective for the LNCaP lineage, downregulating Ki-67 and Cyclin D1. In PCa, Ki-67 expression has been related to the Gleason score, lower disease-free survival, tumor invasion into the seminal vesicles, and biochemical recurrence or even death after radical prostatectomy [ 33 ].…”
Section: Discussionsupporting
confidence: 60%
“…[89] The mechanism of anticancer efficacy of copper complexes is typically dependent on their redox activity and induction of reactive oxygen species (ROS), resulting in deadly oxidative stress. [90,91] A recent study demonstrated that copper/ catechol-based metal-organic framework (CuHPT) could release catechol ligands and reductive copper ions Cu(I) in cancer cells, leading to ROS generation via auto-oxidation and Fenton-like reactions. [52] Copper complexes promote ROS generation and oxidative stress and oxidative damage, and therefore lead to the disruption of membranes, DNA cleavage and damage, protein oxidation, and culminating in cell necrosis or apoptosis.…”
Section: Copper Complexes Induce Ros Generationmentioning
confidence: 99%
“…This compound induces alteration of mitochondrial potential, ROS overexpression, cell-cycle arrest (at S- and G2/M phases) and cellular DNA damage followed by apoptosis, which can turn to necrosis at higher concentrations or longer durations of treatments. Interestingly, the Bax/Bcl-2 expression ratios were differently affected in MCF (p53 + , ER + ) and MDA-MB-231 (p53 − , ER − ), thus suggesting a potential genotype-selective mechanism mediated by the p53 protein, which still need to be clarified though [ 62 ].…”
Section: Mixed Cu(ii) Phen-based Complexesmentioning
confidence: 99%